Formação permanente Freireana: análise de um programa de formação de educadoras/es de escolas do campo e contribuições para a reinvenção - Nascimento, Elson Augusto do (2019)
This study analyzes the construction and development of a process of permanent education of rural school educators in the Freire's perspective in order to unveil and present critical contributions, obstacles and possibilities for the reinvention of the practice of teacher education, based on the collaboration of the teachers and the participants of an educational group. As a reference, Freire's thoughts are used and, as theoretical framework, authors who stand in defense of teacher education in a permanent perspective, among which Silva, Saul and Giovedi stand out. These are authors who contribute to the analysis and interpretation of the information produced. This study employed the methodology of participant observation, in a qualitative approach, based on Lüdke and André, Minayo, Chizzotti, Ezpeleta and Rockwell and Brandão, as well as Paulo Freire's propositions. The research proposal was materialized in a project of extension of Freire’s continuous education of teachers at multigraded schools in the municipality of São Domingos do Norte, ES, Brazil. The project was held in eleven meetings, with thirty-eight educators of graded and multigraded elementary schools. The data produced during the research development were grouped in Freire’s categories that correspond to the principles used for the analysis of the moments of deconstruction and construction of the proposal: Freire's permanent education, dialogicity, critical reflection on practice, participation, awareness, politicity, curriculum and transformative praxis, which constitute a conceptual framework of the researcher about Paulo Freire's idea of permanent education. The results show the meaning and relevance of the principles and moments as a way to support the analysis of the process of development of the education program and to overcome hegemonic formative practices.Thus, we sought to analyze if the moments account for Freire's educational principles; if the practices contribute to the subjects' understanding about the “continued” education from a permanent perspective; and if they favor a transforming praxis of those involved in relation to teacher education, thus showing emancipatory values of teaching and harbingering changes in practice. This research is a contribution to an axis full of needs and it is materialized as a proposal of the education process that becomes a paradigm break and critical reflection on teacher education policies and practices. It presents itself as a possibility to think about the neglect and the domain of teacher education for Rural Education from a market model, detached from the concrete reality of this modality. As a product, it is shown a reinvention of fundamentals and methodological indications in order to contribute to the formation of educators of Rural Education, having Freire's fundamentals and categories as reference, in a critical-liberating perspective, outlined by principles, conditions and necessary moments for a Permanent Educational Program for Rural Educators.